INTERNET MARKETING STRATEGI UNTUK MENINGKATKAN PEMASARAN INDUSTRI KOPIAH SONGKOK DESA BANDAR AGUNG KECAMATAN LUBUK BATANG OKU (OGAN KOMERING ULU) PROVINSI SUMATERA SELATAN - Andela Anggleni; Yofitri Heny Wahyuli; Marina Malian; Ahmad Yani Kosali (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service is the implementation of the Tridharma of higher education to help the community. This community service is to find the problems faced by the Songkok coffee industry, Bandar Agung village, Lubuk Batang sub-district. In terms of marketing, the skullcap industry is still not very effective, because they only market in the neighborhood around the village, where in fact many people in Bandar Agung, Lubuk Batang sub-district, use skullcaps every day. Therefore, the aim of our Community Service is to introduce marketing methods that are more widespread and of course also cost-effective, namely by selling using online media, publishing on social media, and through e-commerce media. Service activities are assisted by students as well as entrepreneurship learning for students as entrepreneurial knowledge. The innovation carried out is to develop marketing through E-commerce based media which aims to expand the market segment of the skullcap industry. From the results of the dedication, a website and telegram were obtained which were used as addresses for online marketing of Bandar Agung Resam coffee beans, Lubuk Batang sub-district, thereby expanding the market share of the Bandar Agung Songkok coffee business, Lubuk Batang sub-district in the new normal period.